Facile, environmentally benign and scalable approach to produce pristine few layers graphene suitable for preparing biocompatible polymer nanocomposites - George, Gejo; Sisupal, Suja Bhargavan; Tomy, Teenu; Kumaran, Alaganandam; Vadivelu, Prabha; Suvekbala, Vemparthan; Sivaram, Swaminathan; Ragupathy, Lakshminarayanan (Scientific Reports, 2018)
The success of developing graphene based biomaterials depends on its ease of synthesis, use of environmentally benign methods and low toxicity of the chemicals involved as well as biocompatibility of the final products/devices. We report, herein, a simple, scalable and safe method to produce defect free few layers graphene using naturally available phenolics i.e. curcumin/tetrahydrocurcumin/ quercetin, as solid-phase exfoliating agents with a productivity of similar to 45 g/batch (D/G = 0.54 and D/D' <= 1.23). The production method can also be employed in liquid-phase using a ball mill (20 g/batch, D/G <= 0.23 and D/D' <= 1.12) and a sand grinder (10 g/batch, D/G <= 0.11 and D/D similar to = 0.78). The combined effect of p-p interaction and charge transfer (from curcumin to graphene) is postulated to be the driving force for efficient exfoliation of graphite. The yielded graphene was mixed with the natural rubber (NR) latex to produce thin film nanocomposites, which show superior tensile strength with low modulus and no loss of % elongation at break. In-vitro and in-vivo investigations demonstrate that the prepared nanocomposite is biocompatible. This approach could be useful for the production of materials suitable in products (gloves/condoms/catheters), which come in contact with body parts/ body fluids.